Metabolic responses to Lactobacillus plantarum contamination or bacteriophage treatment in Saccharomyces cerevisiae using a GC–MS-based metabolomics approach - Feng-Xia Cui; Rui-Min Zhang; Hua-Qing Liu; Yan-Feng Wang; Hao Li (World Journal of Microbiology and Biotechnology, 2015)

Cloning and Functional Analysis of Thylakoidal Ascorbate Peroxidase (TAPX) Gene in Sugarcane - Sheng Wang; Kun-Kun Zhang; Xing Huang; Yan-Jiao Fan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Flow regime of the three outlets on the south bank of Jingjiang River, China: an impact assessment of the Three Gorges Reservoir for 2003–2010 - Rui Zhang; Shuang-hu Zhang; Wei Xu; Ben-de Wang; Hao Wang (Stochastic Environmental Research and Risk Assessment, 2015)

Cotton mitogen-activated protein kinase4 (GhMPK4) confers the transgenic Arabidopsis hypersensitivity to salt and osmotic stresses - Na-Na Wang; Li–Li Zhao; Rui Lu; Yang Li; Xue-Bao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Multiple Responsive Polymer-Peptide Bioconjugate - Xi-Rui Zhou; Rui Ge; Guofeng Li; Long Chen; Tianwei Tan; Xing Wang; Shi-Zhong Luo (International Journal of Peptide Research and Therapeutics, 2015)

Molecular identification and expression of the Foxl2 gene during gonadal sex differentiation in northern snakehead Channa argus - Dan-Dan Wang; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Fish Physiology and Biochemistry, 2015)

Hydrolysis and volatile fatty acids accumulation of waste activated sludge enhanced by the combined use of nitrite and alkaline pH - Cheng Huang; Congcong Liu; Xiuyun Sun; Yinglu Sun; Rui Li; Jiansheng Li; Jinyou Shen; Weiqing Han; Xiaodong Liu; Lianjun Wang (Environmental Science and Pollution Research, 2015)

Fecal Bacterial Composition of the Endangered Yangtze Finless Porpoises Living Under Captive and Semi-natural Conditions - Xiaoling Wan; Rui Ruan; Richard William McLaughlin; Yujiang Hao; Jinsong Zheng; Ding Wang (Current Microbiology, 2015)

Decadal changes in tropical cyclone activity over the western North Pacific in the late 1990s - Haozhe He; Jing Yang; Daoyi Gong; Rui Mao; Yuqing Wang; Miaoni Gao (Climate Dynamics, 2015)

Curcumin Promotes Cell Cycle Arrest and Inhibits Survival of Human Renal Cancer Cells by Negative Modulation of the PI3K/AKT Signaling Pathway - Hao Zhang; Weili Xu; Baolin Li; Kai Zhang; Yudong Wu; Haidong Xu; Junyong Wang; Jun Zhang; Rui Fan; Jinxing Wei (Cell Biochemistry and Biophysics, 2015)

Analysis of Mineral Elements, Metabolism, and Inflammation Indexes in the Plasma of Dairy Cows Suffering from Different Degrees of Lameness - Dongbo Sun; Chunqiu Li; Cheng Gu; Jianfei Chen; Yongli Qu; Xinyu Wang; Jing Gao; Shan Wei; Jianfa Wang; Rui Wu; Donghua Guo (Biological Trace Element Research, 2015)

Antimicrobial activity of human β-defensins against lactic acid bacteria - Xiao-Fang Wang; Fei Tian; Rui-Ming Cao; Jing Li; Sheng-Mei Wu; Xiao-Kui Guo; Tong-Xin Chen (Natural Product Research, 2015)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Transcriptome profiling reveals auxin suppressed anthocyanin biosynthesis in red-fleshed apple callus (Malus sieversii f. niedzwetzkyana) - Xiao-Hao Ji; Rui Zhang; Nan Wang; Long Yang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Candidate gene prediction via quantitative trait locus analysis of fruit shape index traits in apple - Ke Cao; Yuansheng Chang; Rui Sun; Fei Shen; Ting Wu; Yi Wang; Xinzhong Zhang; Zhenhai Han (Euphytica, 2015)

Distribution of the Vrn-D1b allele associated with facultative growth habit in Chinese wheat accessions - Xian-rui Guo; Yuan-yuan Wang; Ling-zhi Meng; Hong-wei Liu; Li Yang; Yang Zhou; Hong-jun Zhang (Euphytica, 2015)

Tempo-spatial analysis of water quality in tributary bays of the Three Gorges Reservoir region (China) - Jialiang Tang; Tao Wang; Bo Zhu; Pei Zhao; Yi Xiao; Rui Wang (Environmental Science and Pollution Research, 2015)

Molecular cloning and characterization of caffeic acid 3-O-methyltransferase from the rhizome of Ligusticum chuanxiong - Juan-Juan Li; Gan Zhang; Ji-hua Yu; Yang-yang Li; Xin-he Huang; Wan-Jun Wang; Rui Tan; Jia-yu Zhou; Hai Liao (Biotechnology Letters, 2015)

Effect of hydrogen sulfide on D1 protein in wheat under drought stress - Hua Li; Ming Quan Gao; Rui Li Xue; Dan Wang; Hui Jie Zhao (Acta Physiologiae Plantarum, 2015)

Zonal overturning circulation and heat flux induced by heaving modes in the world oceans - Wei Tan; Rui Xin Huang; Weiqiang Wang; Xin Wang (Acta Oceanologica Sinica, 2015)

The macroecology of phylogenetically structured hummingbird–plant networks - Ana M. Martín González; Bo Dalsgaard; David Nogués‐Bravo; Catherine H. Graham; Matthias Schleuning; Pietro K. Maruyama; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Severino Mendes de Azevedo; Andrea C. Baquero; et al. (Global Ecology and Biogeography, 2015)
Aim To investigate the association between hummingbird–plant network structure and species richness, phylogenetic signal on species' interaction pattern, insularity and historical and current climate. Location Fifty‐four communities along a c . 10,000 km latitudinal gradient across the A mericas (39° N –32° S ), ranging from sea level to c . 3700 m a.s.l., located on the mainland and on islands and covering a wide range of climate regimes. Methods We measured the level of specialization and modularity in mutualistic plant–hummingbird interaction networks. Using an ordinary least squares multimodel approach, we examined the influence of species richness, phylogenetic signal, insularity and current and historical climate conditions on network structure (null‐model‐corrected specialization and modularity). Results Phylogenetically related species, especially plants, showed a tendency to interact with a similar array of mutualistic partners. The spatial variation in network structure exhibited a constant association with species phylogeny ( R 2 = 0.18–0.19); however, network structure showed the strongest association with species richness and environmental factors ( R 2 = 0.20–0.44 and R 2 = 0.32–0.45, respectively). Specifically, higher levels of specialization and modularity were associated with species‐rich communities and communities in which closely related hummingbirds visited distinct sets of flowering species. On the mainland, specialization was also associated with warmer temperatures and greater historical temperature stability. Main conclusions Our results confirm the results of previous macroecological studies of interaction networks which have highlighted the importance of species richness and the environment in determining network structure. Additionally, for the first time, we report an association between network structure and species phylogenetic signal at a macroecological scale, indicating that high specialization and modularity are associated with high interspecific competition among closely related hummingbirds, subdividing the floral niche. This suggests a tighter co‐evolutionary association between hummingbirds and their plants than in previously studied plant–bird mutualistic systems.

A new highly oxygenated daphnane diterpene esters from the flower buds of Daphne genkwa - Hai-Long Jiang; Rui Wang; Jian-Yong Li; Yan-Ping Shi (Natural Product Research, 2015)

Combined drought and heat stress in Camellia oleifera cultivars: leaf characteristics, soluble sugar and protein contents, and Rubisco gene expression - Baoming Wang; Jianjun Chen; Longsheng Chen; Xiangnan Wang; Rui Wang; Li Ma; Shaofeng Peng; Jian Luo; Yongzhong Chen (Trees, 2015)

Effect of irrigation on the soil respiration of constructed grasslands in Inner Mongolia, China - Ji–Rui Gong; Sha Xu; Yihui Wang; Qinpu Luo; Min Liu; Wei Zhang (Plant and Soil, 2015)

Endogenous level of TIGAR in brain is associated with vulnerability of neurons to ischemic injury - Lijuan Cao; Jieyu Chen; Mei Li; Yuan-Yuan Qin; Meiling Sun; Rui Sheng; Feng Han; Guanghui Wang; Zheng-Hong Qin (Neuroscience Bulletin, 2015)

Retraction Note to: Meta-analysis of the relationship between single nucleotide polymorphism rs72689236 of caspase-3 and Kawasaki disease - Yanlin Xing; Hong Wang; Xiaomei Liu; Xianyi Yu; Rui Chen; Ce Wang; Xuexin Yu; Le Sun (Molecular Biology Reports, 2015)

Retraction Note to: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2015)

Mutations in human IFT140 cause non-syndromic retinal degeneration - Mingchu Xu; Lizhu Yang; Feng Wang; Huajin Li; Xia Wang; Weichen Wang; Zhongqi Ge; Keqing Wang; Li Zhao; Hui Li; Yumei Li; Ruifang Sui; et al. (Human Genetics, 2015)

The processes of graft union formation in tomato - Jingwei Fan; Rui Yang; Xiaoman Li; Wenchao Zhao; Fukuan Zhao; Shaohui Wang (Horticulture, Environment, and Biotechnology, 2015)

Effect of Dietary Selenomethionine Supplementation on Growth Performance, Tissue Se Concentration, and Blood Glutathione Peroxidase Activity in Kid Boer Goats - Yu-xuan Song; Jin-xing Hou; Lei Zhang; Jian-gang Wang; Xiao-rui Liu; Zhan-qin Zhou; Bin-yun Cao (Biological Trace Element Research, 2015)

The carbohydrate metabolism of scallop Chlamys farreri in the immune response against acute challenge of Vibrio anguillarum - Xingqiang Wang; Lingling Wang; Huan Zhang; Rui Liu; Linsheng Song (Aquaculture International, 2015)

DNA methylation level of promoter region of activating transcription factor 5 in glioma - Xiao-min Hua; Juan Wang; Dong-meng Qian; Jing-yi Song; Hao Chen; Xiu-li Zhu; Rui Zhou; Yu-dan Zhao; Xiu-zhi Zhou; Ling Li; Li Zhang; Xu-xia Song; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Regulation of three isoforms of SOD gene by environmental stresses in citrus red mite, Panonychus citri - Ying-Cai Feng; Chong-Yu Liao; Wen-Kai Xia; Xuan-Zhao Jiang; Feng Shang; Guo-Rui Yuan; Jin-Jun Wang (Experimental and Applied Acarology, 2015)

Erratum to: Characterization of carbonaceous aerosols at Mount Lu in South China: implication for secondary organic carbon formation and long-range transport - Peng-hui Li; Yan Wang; Tao Li; Lei Sun; Xianliang Yi; Li-qiong Guo; Rui-hong Su (Environmental Science and Pollution Research, 2015)

Characterization of carbonaceous aerosols at Mount Lu in South China: implication for secondary organic carbon formation and long-range transport - Peng-hui Li; Yan Wang; Tao Li; Lei Sun; Xianliang Yi; Li-qiong Guo; Rui-hong Su (Environmental Science and Pollution Research, 2015)

Predicting invasions of Wedelia trilobata (L.) Hitchc. with Maxent and GARP models - Zhong Qin; Jia-en Zhang; Antonio DiTommaso; Rui-long Wang; Rui-shan Wu (Journal of Plant Research, 2015)

Impacts of ecological restoration and human activities on habitat of overwintering migratory birds in the wetland of Poyang Lake, Jiangxi Province, China - Chuan-zhun Sun; Lin Zhen; Chao Wang; Bang-you Yan; Xiao-chang Cao; Rui-zi Wu (Journal of Mountain Science, 2015)

Cloning and analysis of β-amyrin synthase gene in Bupleurum chinense - Ke Gao; Su-rui Wu; Ling Wang; Yan-hong Xu; Jian-he Wei; Chun Sui (Genes & Genomics, 2015)

Effect of mowing on N2O and CH4 fluxes emissions from the meadow-steppe grasslands of Inner Mongolia - Zedong Lu; Rui Du; Pengrui Du; Ziming Li; Zongmin Liang; Yaling Wang; Saisai Qin; Lei Zhong (Frontiers of Earth Science, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

GRY79 encoding a putative metallo-β-lactamase-trihelix chimera is involved in chloroplast development at early seedling stage of rice - Chunmei Wan; Chunmei Li; Xiaozhi Ma; Yang Wang; Changhui Sun; Rui Huang; Ping Zhong; Zhiyan Gao; Dan Chen; Zhengjun Xu; Jianqing Zhu; Xiaoling Gao; et al. (Plant Cell Reports, 2015)

Activation of VEGF/Flk-1-ERK Pathway Induced Blood–Brain Barrier Injury After Microwave Exposure - Li-Feng Wang; Xiang Li; Ya-Bing Gao; Shui-Ming Wang; Li Zhao; Ji Dong; Bin-Wei Yao; Xin-Ping Xu; Gong-Min Chang; Hong-Mei Zhou; Xiang-Jun Hu; Rui-Yun Peng (Molecular Neurobiology, 2015)

Prioritizing Genes Related to Nicotine Addiction Via a Multi-source-Based Approach - Xinhua Liu; Meng Liu; Xia Li; Lihua Zhang; Rui Fan; Ju Wang (Molecular Neurobiology, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Protective enzymes and genes related to the JA pathway are involved in the response to root-knot nematodes at high soil temperatures in tomatoes carrying Mi-1 - Canli Hu; Wenchao Zhao; Jingwei Fan; Zilong Li; Rui Yang; Fukuan Zhao; JianLi Wang; Shaohui Wang (Horticulture, Environment, and Biotechnology, 2015)

Activin A can induce definitive endoderm differentiation from human parthenogenetic embryonic stem cells - Zhiqiang Wang; Wenliang Li; Tianxing Chen; Jun Yang; Zhengqi Wen; Xinmin Yan; Tao Shen; Rui Liang (Biotechnology Letters, 2015)

Cytochrome P450 2D6 genotype affects the pharmacokinetics of controlled-release paroxetine in healthy Chinese subjects: comparison of traditional phenotype and activity score systems - Rui Chen; Haotian Wang; Jun Shi; Kai Shen; Pei Hu (European Journal of Clinical Pharmacology, 2015)

Porcine epidemic diarrhea virus uses cell-surface heparan sulfate as an attachment factor - Chang-chao Huan; Yue Wang; Bo Ni; Rui Wang; Li Huang; Xiao-feng Ren; Guang-zhi Tong; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2015)

Tree‐ring reconstruction of July–May precipitation ( AD 1816–2010) in the northwestern marginal zone of the East Asian summer monsoon reveals the monsoon‐related climate signals - Feng Chen; Huiqin Wang; Fa‐hu Chen; Yujiang Yuan; Rui‐bo Zhang (International Journal of Climatology, 2015)
A July–May precipitation reconstruction for the period AD 1816–2010 was developed from a tree‐ring width chronology of Picea wilsonii for the Xinglong Mountains area of Lanzhou. The reconstruction explains 55.8% of the actual precipitation variance during the calibration period from 1951 to 2010. Wet conditions prevailed during the periods 1822–1835, 1843–1858, 1870–1877, 1884–1891, 1911–1921, 1933–1938, 1944–1979 and 2009–2010. Dry episodes occurred during 1816–1821, 1836–1842, 1859–1869, 1878–1883, 1892–1910, 1922–1932, 1939–1943 and 1980–2008. Multi‐taper method spectral analysis indicates the existence of some significant peaks at 2.8, 3.0 and 3.5 years. Spatial correlations with gridded land surface precipitation data revealed that our reconstruction represents regional precipitation signal for a large area of North China linked to the East Asian summer monsoon (EASM). Comparison with other tree‐ring‐based precipitation/drought reconstructions from surrounding areas implies a high degree of confidence for our reconstruction. Precipitation variations in the study area are significantly correlated with sea surface temperatures in eastern equatorial Pacific Ocean and tropical western Pacific Ocean, suggesting a possible connection of regional precipitation variations to the EASM and the El Niño‐Southern Oscillation (ENSO).

Heterogeneity of Bacterial Community Compositions in Surface Sediments of Three Lake Zones in Lake Taihu - Rui Huang; Dayong Zhao; Cuiling Jiang; Meng Wang (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

(Z)-3-Hexenal, One of the Green Leaf Volatiles, Increases Susceptibility of Rice to the White-Backed Planthopper Sogatella furcifera - Baohui Wang; Guoxin Zhou; Zhaojun Xin; Rui Ji; Yonggen Lou (Plant Molecular Biology Reporter, 2015)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Evaluation of miRNA-binding-site SNPs of MRE11A, NBS1, RAD51 and RAD52 involved in HRR pathway genes and risk of breast cancer in China - Zhenzhen Wu; Peng Wang; Chunhua Song; Kaijuan Wang; Rui Yan; Jingruo Li; Liping Dai (Molecular Genetics and Genomics, 2015)

Effects of alfalfa saponin extract on mRNA expression of Ldlr, LXRα, and FXR in BRL cells - Xin-ping Liang; Dong-qiang Zhang; Yan-yan Chen; Rui Guo; Jie Wang; Cheng-zhang Wang; Ying-hua Shi (Journal of Zhejiang University-SCIENCE B, 2015)

Higenamine regulates Nrf2-HO-1-Hmgb1 axis and attenuates intestinal ischemia–reperfusion injury in mice - Chao Liu; Chenyu Zhu; Guangsheng Wang; Rui Xu; Yaoming Zhu (Inflammation Research, 2015)

Decreased expression of microRNA-125a-3p upregulates interleukin-23 receptor in patients with Hashimoto’s thyroiditis - Huiyong Peng; Yingzhao Liu; Jie Tian; Jie Ma; Xinyi Tang; Jun Yang; Ke Rui; Yue Zhang; Chaoming Mao; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Quantitative trait locus mapping for seed dormancy in different post-ripening stages in a Tibetan semi-wild wheat (Triticum aestivum ssp. tibetanum Shao) - Yun-Feng Jiang; Ji-Rui Wang; Wei Luo; Yu-Ming Wei; Peng-Fei Qi; Ya-Xi Liu; Qian-Tao Jiang; Yuan-Ying Peng; Guo-Yue Chen; Shou-Fen Dai; You-Liang Zheng; Xiu-Jin Lan (Euphytica, 2015)

Mycobacterium smegmatis MSMEG_3705 Encodes a Selective Major Facilitator Superfamily Efflux Pump with Multiple Roles - Zhen Zhang; Rui Wang; Jianping Xie (Current Microbiology, 2015)

A simple and rapid approach to manipulate pseudorabies virus genome by CRISPR/Cas9 system - Aotian Xu; Chao Qin; Yue Lang; Mingyue Wang; Mengyang Lin; Chuang Li; Rui Zhang; Jun Tang (Biotechnology Letters, 2015)

Review and evaluation of China’s standards and regulations on the fuel consumption of motor vehicles - Yue-Fu Jin; Zhao Wang; Hui-Ming Gong; Tian-Lei Zheng; Xiang Bao; Jia-Rui Fan; Michael Wang; Miao Guo (Mitigation and Adaptation Strategies for Global Change, 2015)

Spatial-temporal patterns of major ion chemistry and its controlling factors in the Manasarovar Basin, Tibet - Zhijun Yao; Rui Wang; Zhaofei Liu; Shanshan Wu; Liguang Jiang (Journal of Geographical Sciences, 2015)

Mineralogy and isotope geochemical characteristics for Xiaozhen copper deposit, Langao County, Shaanxi Province and their constraint on genesis of the deposit - Gang Wang; Zong-qi Wang; Rui Shi; Ying-li Zhang; Kun-ming Wang (Geosciences Journal, 2015)

Marinactinospora endophytica sp. nov., isolated from a medicinal plant - Min-Jiao Liu; Thi-Nhan Khieu; Rui Gao; Wael N. Hozzein; Hong-Fei Wang; Wei Yang; Salam Nimaichand; Zhi Xiong; Yan-Qing Duan; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

Burkholderia metalliresistens sp. nov., a multiple metal-resistant and phosphate-solubilising species isolated from heavy metal-polluted soil in Southeast China - Jun Kang Guo; Yong Zhen Ding; Ren Wei Feng; Rui Gang Wang; Ying Ming Xu; Chun Chen; Xiu Li Wei; Wei Min Chen (Antonie van Leeuwenhoek, 2015)

A novel method for rapid in vivo induction of homogeneous polyploids via calluses in a woody fruit tree (Ziziphus jujuba Mill.) - Qing-Hua Shi; Ping Liu; Meng-Jun Liu; Jiu-Rui Wang; Juan Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Comparative genomic approach reveals novel conserved microRNAs in Inner Mongolia cashmere goat skin and longissimus dorsi - Rui Su; Shaoyin Fu; Yanjun Zhang; Ruijun Wang; Yanhong Zhou; Jinquan Li; Wenguang Zhang (Molecular Biology Reports, 2015)

MiR-1224-5p acts as a tumor suppressor by targeting CREB1 in malignant gliomas - Jin Qian; Rui Li; Ying-Yi Wang; Yan Shi; Wen-Kang Luan; Tao Tao; Jun-Xia Zhang; Yi-Chang Xu; Yong-Ping You (Molecular and Cellular Biochemistry, 2015)

GITRL as a genetic adjuvant enhances enterovirus 71 VP1 DNA vaccine immunogenicity - Jing Yuan; Xinyi Tang; Kai Yin; Jie Tian; Ke Rui; Jie Ma; Chaoming Mao; Jianguo Chen; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Distribution, bioavailability, and potential ecological risk of Cu, Pb, and Zn in soil in a potential groundwater source area - Yanguo Teng; Dan Feng; Jin Wu; Rui Zuo; Liuting Song; Jinsheng Wang (Environmental Monitoring and Assessment, 2015)

Village network centrality in rural tourism destination: A case from Yesanpo tourism area, China - Rui-ying Zhang; Jian-chao Xi; Shou-kun Wang; Xin-ge Wang; Quan-sheng Ge (Journal of Mountain Science, 2015)

Cloning and expression analysis of phenylalanine ammonia-lyase (PAL) gene family and cinnamate 4-hydroxylase (C4H) from Dryopteris fragrans - Yan Li; Lili Sun; Hemeng Wang; Rui Gao; Junzheng Zhang; Baozhong Hu; Ying Chang (Biologia, 2015)

PtAKT1 maintains selective absorption capacity for K+ over Na+ in halophyte Puccinellia tenuiflora under salt stress - Pei Wang; Qiang Guo; Qian Wang; Xiang-Rui Zhou; Suo-Min Wang (Acta Physiologiae Plantarum, 2015)

Isolation of a new lycodine alkaloid from Lycopodium japonicum - Jichun Wu; Huanqin Wang; Yanfang Ma; Jinhe Jiang; Rui Zhan; Yegao Chen (Natural Product Research, 2015)

Dependence of shrub canopy water storage on raindrop size in revegetated desert - Xin-ping Wang; Hao Zhang; Ya-feng Zhang; Rui Hu; Yan-xia Pan (Hydrological Sciences Journal, 2015)

Estimation of soil erosion in some sections of Lower Jinsha River based on RUSLE - Liguang Jiang; Zhijun Yao; Zhaofei Liu; Shanshan Wu; Rui Wang; Lei Wang (Natural Hazards, 2015)

Characterization of the amino acid composition of soils under organic and conventional management after addition of different fertilizers - Pablo Gonzalez Perez; Rui Zhang; Xiaoli Wang; Jun Ye; Danfeng Huang (Journal of Soils and Sediments, 2015)

Inhibiting β-Amyloid-Associated Alzheimer’s Pathogenesis In Vitro and In Vivo by a Multifunctional Dimeric Bis(12)-hupyridone Derived from Its Natural Analogue - Shengquan Hu; Rui Wang; Wei Cui; Zaijun Zhang; Shinghung Mak; Daping Xu; Chunglit Choi; Karl Wahkeung Tsim; Paul R. Carlier; Mingyuen Lee; Yifan Han (Journal of Molecular Neuroscience, 2015)

Factors controlling the long-term temporal and spatial patterns of nitrate-nitrogen export in a dairy farming watershed - Rui Jiang; Chun-ying Wang; Ryusuke Hatano; Kanta Kuramochi; Atsushi Hayakawa; Krishna P. Woli (Environmental Monitoring and Assessment, 2015)

Isolation and in silico characterization of a shikimate kinase from Cassia obtusifolia - Zubi Liu; Qiankun Zhu; Yangyang Li; Jihua Yu; Wanjun Wang; Rui Tan; Jiayu Zhou; Hai Liao (Acta Physiologiae Plantarum, 2015)

Isolation, Characterization and Promoter Analysis of Cell Wall Invertase Gene SoCIN1 from Sugarcane (Saccharum spp.) - Jun-Qi Niu; Ai-Qin Wang; Jing-Li Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Molecular Cloning and Functional Analysis of an Ethylene Receptor Gene from Sugarcane (Saccharum spp.) by Hormone and Environmental Stresses - Ai-Qin Wang; Xing-Zhi Ye; Jing-Li Huang; Jun-Qi Niu; Ming Liu; Yong-Bao Pan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

Tumor Necrosis Factor-Related Apoptosis Inducing Ligand Gene Polymorphisms are Correlated with Gastric Cancer in Central China - Changgao Wang; Shufang Xu; Fengming Yi; Xiaobing Wang; Yuan Lei; Sha Huang; Rui Zhou; Bing Xia (Pharmaceutical Research, 2015)

Effect of grazing on the abundance of functional genes associated with N cycling in three types of grassland in Inner Mongolia - K. Ding; L. Zhong; X. P. Xin; Z. H. Xu; X. M. Kang; W. J. Liu; Y. C. Rui; L. L. Jiang; L. Tang; Y. F. Wang (Journal of Soils and Sediments, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Solubilization of 4,4′-dibromodiphenyl ether under combined TX-100 and cosolvents - Xingjian Yang; Guining Lu; Rui Wang; Chuling Guo; Hongliang Zhang; Zhi Dang (Environmental Science and Pollution Research, 2015)

Inhibition of Microtubule Dynamics Affects Podosome Belt Formation During Osteoclast Induction - Yunfan Ti; Lingjun Zhou; Rui Wang; Jianning Zhao (Cell Biochemistry and Biophysics, 2015)

Historic water consumptions and future management strategies for Haihe River basin of Northern China - Xiao-jun Wang; Jian-yun Zhang; Zhi-feng Yang; Shamsuddin Shahid; Rui-min He; Xing-hui Xia; Hong-wei Liu (Mitigation and Adaptation Strategies for Global Change, 2015)

Recent climate warming of central China reflected by temperature-sensitive tree growth in the eastern Qinling Mountains and its linkages to the Pacific and Atlantic oceans - Feng Chen; Rui-bo Zhang; Hui-qin Wang; Li Qin (Journal of Mountain Science, 2015)

A novel missense mutation in collagenous domain of EDA gene in a Chinese family with X-linked hypohidrotic ectodermal dysplasia - DAXU LI; RAN XU; FUMENG HUANG; BIYUAN WANG; YU TAO; ZIJIAN JIANG; HAIRUI LI; JIANFENG YAO; PENG XU; XIAOKANG WU; LE REN; RUI ZHANG; et al. (Journal of Genetics, 2015)

China’s provincial CO2 emissions embodied in trade with implications for regional climate policy - Zhangqi Zhong; Rui Huang; Qinneng Tang; Xiaonan Cong; Zheng Wang (Frontiers of Earth Science, 2015)

In Vivo Antioxidant Effects of Hydrolysate Derived from Waste Proteins of Mactra veneriformis - Rui Liu; Lingchong Wang; Wenwen Zheng; Hao Wu (Journal of Aquatic Food Product Technology, 2015)

Optimization of the expression conditions of CGA-N46 in Bacillus subtilis DB1342(p-3N46) by response surface methodology - Rui-Fang Li; Bin Wang; Shuai Liu; Shi-Hua Chen; Guang-Hai Yu; Shuo-Ye Yang; Liang Huang; Yan-Li Yin; Zhi-Fang Lu (Interdisciplinary Sciences: Computational Life Sciences, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Assessing winter oilseed rape freeze injury based on Chinese HJ remote sensing data - Bao She; Jing-feng Huang; Rui-fang Guo; Hong-bin Wang; Jing Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Next-generation sequencing-based molecular diagnosis of 82 retinitis pigmentosa probands from Northern Ireland - Li Zhao; Feng Wang; Hui Wang; Yumei Li; Sharon Alexander; Keqing Wang; Colin E. Willoughby; Jacques E. Zaneveld; Lichun Jiang; Zachry T. Soens; Philip Earle; David Simpson; et al. (Human Genetics, 2015)

Hydrogen sulfide alleviates the aluminum-induced changes in Brassica napus as revealed by physiochemical and ultrastructural study of plant - Basharat Ali; Ping Qian; Rui Sun; Muhammad A. Farooq; Rafaqat A. Gill; Jian Wang; Muhammad Azam; Weijun Zhou (Environmental Science and Pollution Research, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

The Influence of Land Use on the Abundance and Diversity of Ammonia Oxidizers - Dayong Zhao; Juan Luo; Jianqun Wang; Rui Huang; Kun Guo; Yi Li; Qinglong L. Wu (Current Microbiology, 2015)

Impact of heavy metal stresses on the growth and auxin homeostasis of Arabidopsis seedlings - Rui Wang; Jiehua Wang; Lin Zhao; Shaohui Yang; Yingjin Song (BioMetals, 2015)

Over-expression of the MxIRT1 gene increases iron and zinc content in rice seeds - Song Tan; Rui Han; Peng Li; Guang Yang; Shuang Li; Peng Zhang; Wei-Bing Wang; Wei-Zhong Zhao; Li-Ping Yin (Transgenic Research, 2015)

Chemical modification, characterization and bioactivity of a released exopolysaccharide (r-EPS1) from Lactobacillus plantarum 70810 - Kun Wang; Wei Li; Xin Rui; Teng Li; Xiaohong Chen; Mei Jiang; Mingsheng Dong (Glycoconjugate Journal, 2015)

Phylogenetic relationships among Elymus and related diploid genera (Triticeae: Poaceae) based on nuclear rDNA ITS sequences - Gang Gao; Jia-bin Deng; Xue-mei Gou; Qian Wang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2015)

Gaseous NO2 effects on stomatal behavior, photosynthesis and respiration of hybrid poplar leaves - Yanbo Hu; Nacer Bellaloui; Mulualem Tigabu; Jinghong Wang; Jian Diao; Ke Wang; Rui Yang; Guangyu Sun (Acta Physiologiae Plantarum, 2015)

Two new flavonol glycosides from Dimocarpus longan leaves - Yongmei Xue; Wenjing Wang; Yujiao Liu; Rui Zhan; Yegao Chen (Natural Product Research, 2015)

Functional analysis of OsPGIP1 in rice sheath blight resistance - Rui Wang; Liaoxun Lu; Xuebiao Pan; Zongliang Hu; Fei Ling; Yan Yan; Yemao Liu; Yongjun Lin (Plant Molecular Biology, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Gelsolin: Role of a Functional Protein in Mitigating Radiation Injury - Mingjuan Li; Fengmei Cui; Ying Cheng; Ling Han; Jia Wang; Ding Sun; Yu-long Liu; Ping-kun Zhou; Rui Min (Cell Biochemistry and Biophysics, 2015)

Contribution weight of engineering technology on pollutant emission reduction based on IPAT and LMDI methods - Hairti Tursun; Zhenyang Li; Rui Liu; Yuan Li; Xiaohui Wang (Clean Technologies and Environmental Policy, 2015)

H2O2 Induces Myocardial Hypertrophy in H9c2 Cells: A Potential Role of Ube3a - Rui Song; Jie Zhang; Lijuan Zhang; Guanghua Wang; Da Wo; Jian Feng; Xucheng Li; Jue Li (Cardiovascular Toxicology, 2015)

Potential impact of climate change on future water demand in Yulin city, Northwest China - Wang Xiao-jun; Zhang Jian-yun; Shahid Shamsuddin; He Rui-min; Xia Xing-hui; Mou Xin-li (Mitigation and Adaptation Strategies for Global Change, 2015)

Expression Analysis of Two P450 Monooxygenase Genes of the Tobacco Cutworm Moth (Spodoptera litura) at Different Developmental Stages and in Response to Plant Allelochemicals - Rui-Long Wang; Jun Li; Christian Staehelin; Xiao-Wei Xin; Yi-Juan Su; Ren-Sen Zeng (Journal of Chemical Ecology, 2015)

3-D observations of a red tide event in the offshore water along the western Guangdong coast - Lingling Xie; Qingxiang Chen; Jianyu Hu; Shuwen Zhang; Xiaofei Yi; Fajin Chen; Rui Deng; Xiaodong Deng; Jing Wang; Yiquan Qi (Acta Oceanologica Sinica, 2015)